Bilateral Lung Transplantation for Congenital Pulmonary Arteriovenous Fistula with Intraoperative Venovenous ECMO Support: The First Case Report in China - Liang, Jialong; Chen, Yuan; Zhou, Jintao; Zheng, Mingfeng; Liu, Feng; Ye, Shugao; Chen, Jingyu; Ji, Yong (Frontiers in Surgery, 2022)
Pulmonary arteriovenous fistula (PAVF) is a rare pulmonary vascular lesion, more than 80% of which are caused by congenital abnormal development of pulmonary capillaries. The incidence of PAVF ranges from 2/100,000 to 3/100,000, with no difference in male and female ratio. Congenital PAVF is often associated with hereditary hemorrhagic telangiectasia (HHT). In this article, we report a patient with only congenital PAVF that was successfully treated by bilateral lung transplantation (BLT) with intraoperative veno-venous ECMO support because both lungs have been affected by PAVF and secondary pulmonary hypertension. To the best or our knowledge, this is the first report of a BLT for PAVF in China, and this is the second report that explains the clinical course of a patient to receive BLT for congenital PAVF without HHT. Some investigators have proposed lung transplant as a definitive treatment, but the results are controversial. On the basis of the current condition of this patient, we believe lung transplantation is a viable option for certain patients, but the long-term effect remains to be studied.